Comparison of the Iowa Reference Algorithm to the Heidelberg Spectralis optical coherence tomography segmentation algorithm. Issue 5 (20th February 2020) - Sun, Jasmine Q.; McGeehan, Brendan; Firn, Kim; Irwin, David; Grossman, Murray; Ying, Gui‐Shuang; Kim, Benjamin J.
Abstract: For spectral‐domain optical coherence tomography (SD‐OCT) studies of neurodegeneration, it is important to understand how segmentation algorithms differ in retinal layer thickness measurements, segmentation error locations and the impact of manual correction. Using macular SD‐OCT images of frontotemporal degeneration patients and controls, we compare the individual and aggregate retinal layer thickness measurements provided by two commonly used algorithms, the Iowa Reference Algorithm and Heidelberg Spectralis, with manual correction of significant segmentation errors. We demonstrate small differences of most retinal layer thickness measurements between these algorithms. Outer sectors of the Early Treatment Diabetic Retinopathy Study grid require a greater percent of eyes to be corrected than inner sectors of the retinal nerve fiber layer (RNFL). Manual corrections affect thickness measurements mildly, resulting in at most a 5% change in RNFL thickness. Our findings can inform researchers how to best use different segmentation algorithms when comparing retinal layer thicknesses. Abstract : The purpose of this study is to compare two commonly used spectral‐domain optical coherence tomography segmentation algorithms regarding retinal layer thickness measurements and impact of manual correction in frontotemporal degeneration patients and controls. This study finds that these algorithms provide small differences in retinal layer thicknesses. Manual correction mildly affects thickness measurements and segmentation errors are more common for the outer sectors of the Early Treatment Diabetic Retinopathy Study grid.